Analisis Kebijakan Program Makan Bergizi Gratis (MBG) Perspektif Siyāsah Dustūriyyah - Hasiah, Hasiah (CV Global Research Publication, 2026)
The Free Nutritious Meal Program (MBG) is a strategic policy implemented by the Indonesian government aimed at improving the nutritional quality of society, particularly for vulnerable groups such as school children, toddlers, and pregnant and breastfeeding women. This study analyzes the MBG program from the perspective of siyāsah dustūriyyahusing a qualitative normative method through literature review of Islamic legal theory and public policy sources. The findings indicate that the MBG program has strong legal legitimacy and is aligned with the principles of maslahah and maqasid al-sharia, particularly in preserving life (hifz al-nafs) and lineage (hifz al-nasl). However, its implementation still faces several challenges, including targeting inaccuracy, distribution inequality, and weak supervision, which may lead to potential mafsadat. Therefore, strengthening governance, transparency, and accountability is essential to ensure that the program operates effectively in accordance with the principles of siyāsah dustūriyyah.